2017
DOI: 10.1007/s10518-017-0083-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the in-plane deformability of RC floors with traditional and innovative lightening elements in RC framed and wall structures

Abstract: In this paper, the in-plane deformability of floors in Reinforced Concrete (RC) structures has been investigated in order to establish the role of lightening elements made of both traditional ceiling bricks and Expanded Polystyrene (EPS) blocks. The study has been firstly developed via the implementation of three-dimensional finite element models simulating the real geometry of the floors. The numerical results have been, then, used to assess the thickness of equivalent slabs introduced in three-dimensional fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The fitting values of β are listed in Table 2. It is worth noting that the trend of the curve is similar to those of the curves relating the stiffness index R i ( R i,wall ) to the displacement ratio δ 1 / δ 2 ( δ rig / δ flex ) presented by Pecce et al (2017, 2018); this is because, the shear force and the lateral displacements of the LLREs are strictly related.…”
Section: Resultssupporting
confidence: 61%
“…The fitting values of β are listed in Table 2. It is worth noting that the trend of the curve is similar to those of the curves relating the stiffness index R i ( R i,wall ) to the displacement ratio δ 1 / δ 2 ( δ rig / δ flex ) presented by Pecce et al (2017, 2018); this is because, the shear force and the lateral displacements of the LLREs are strictly related.…”
Section: Resultssupporting
confidence: 61%
“…As shown in Table 3, for a bare frame building, the different in-plane stiffnesses of the diaphragms has a low influence on the frequencies and modal mass ratios; really, the floor can be considered always rigid in framed structures as is well-known (Pecce et al, 2017). In fact, removing the hypothesis of rigid diaphragm and modeling the floors as shell elements with a finite stiffness, there is a negligible variation, <2 and 5% in the case of slab with equivalent thickness (t) equal to 9 and 1 cm, respectively.…”
Section: The Effect Of In-plane Floor Deformability On Rc Bare Framementioning
confidence: 99%
“…In particular, Tena-Colunga et al (2015) investigated the effects of different floor typologies and thicknesses on several buildings. Instead, Pecce et al (2017) analyzed the influence of the lightening elements in RC floors on the in-plane floor deformability. However, the flexibility of the floors is typical in shear wall buildings (Kunnath et al, 1991;Saffarini and Qudaimat, 1992;Ahmadi et al, 2014;Pecce et al, 2019); therefore, the influence of the infill walls on the floor response is an interesting topic that is little studied.…”
Section: The Role Of the In-plane Floor Flexibility On The Dynamic Rementioning
confidence: 99%
“…Moreover, for RC buildings with walls as resisting vertical elements or for masonry buildings, the hypothesis of a rigid floor might not always be reliable, and the actual deformability of the floor should be taken in account in the study of the entire structure; the infill walls and partitions increases the transversal stiffness of the vertical elements with respect to the bare frames, making the floor effect not rigid as in framed buildings . Different numerical studies or studies based on experimental tests have evaluated the effects of flexible diaphragms on building structures, concluding that the flexible diaphragms affect the buildings in two ways: the dynamic characteristics of the buildings, such as natural frequencies, and the lateral load distributions of the seismic action to the vertical resisting elements. Therefore, many studies available in the literature have demonstrated that the infill walls significantly increase the stiffness of structures and subsequently decrease the elastic fundamental period; however, the estimation of this effect is an open problem, and less attention has been given to internal partitions, which are negligible, especially in buildings with flexible frames, such as the ones designed for gravity loads.…”
Section: Literature Reviewmentioning
confidence: 99%